2020
DOI: 10.1249/mss.0000000000002337
|View full text |Cite
|
Sign up to set email alerts
|

Casein Ingestion Does Not Increase Muscle Connective Tissue Protein Synthesis Rates

Abstract: Purpose This study aimed to assess the effect of dietary protein ingestion on intramuscular connective tissue protein synthesis rates during overnight recovery from a single bout of resistance exercise. Methods Thirty-six healthy, young males were randomly assigned to one of three treatments. One group ingested 30 g intrinsically L-[1-13C]-phenylalanine-labeled casein protein before sleep (PRO, n = 12). The other two groups performed a bout of resistanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(35 citation statements)
references
References 40 publications
4
28
3
Order By: Relevance
“…PRO) to be utilized for de novo muscle connective tissue protein synthesis during overnight recovery. The present findings align with our recent work demonstrating that dietary protein-derived amino acids are incorporated into de novo muscle connective tissue protein at rest and, to a further extent, during postexercise recovery in younger individuals (Trommelen et al, 2020). Altogether, these data reinforce our findings that resistance-type exercise promotes the remodeling of muscle connective tissue and illustrate the potential role of dietary protein to support postexercise skeletal muscle tissue adaptation in older individuals.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…PRO) to be utilized for de novo muscle connective tissue protein synthesis during overnight recovery. The present findings align with our recent work demonstrating that dietary protein-derived amino acids are incorporated into de novo muscle connective tissue protein at rest and, to a further extent, during postexercise recovery in younger individuals (Trommelen et al, 2020). Altogether, these data reinforce our findings that resistance-type exercise promotes the remodeling of muscle connective tissue and illustrate the potential role of dietary protein to support postexercise skeletal muscle tissue adaptation in older individuals.…”
Section: Discussionsupporting
confidence: 92%
“…Resistance-type exercise is the most potent anabolic stimulus for skeletal muscle tissue protein. We have recently demonstrated that a bout of resistance-type exercise increases muscle connective tissue protein synthesis rates in younger individuals (Trommelen et al, 2020). As hypothesized in the present study, a bout of resistance-type exercise combined with presleep casein protein ingestion increased postprandial muscle connective tissue protein synthesis rates by ∼100% during overnight recovery in older men (Figure 4a).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…A recent study also reported that intramuscular connective tissue protein synthesis rates were not significantly increased in healthy young males who ingested 30 g of casein protein 30 minutes before sleep following resistance exercise, compared to those who ingested a placebo 23 . A possible reason for these negative results could be the amount of casein protein ingested as 40-48 g of casein protein had positive effects in previous studies 8,9 , whereas only 30 g of casein protein was ingested in the studies showing no effects 22,23 . However, a recent study involving active males and females reported that the ingestion of 40 g of casein protein 30 minutes before sleep after repeated high-intensity drop jumps did not affect acute functional recovery indices such as countermovement jumps or pressure-pain threshold 2 , indicating that the results of the previous studies might not be due to the amount of casein protein ingested alone.…”
Section: Effects Of Pre-sleep Casein Protein On Post-exercise Recoverymentioning
confidence: 95%
“…The use of highly enriched intrinsically labelled protein has consistently shown that dietary protein-derived amino acids are utilised for de novo muscle protein synthesis across a wide variety of populations and can be modulated by various dietary and physiological conditions (3,27,51,52) . Ingested protein delivers amino acids as precursors for de novo muscle protein synthesis in mixed muscle protein (3) , and has also been detected in various isolated muscle protein fractions, such as myofibrillar (51) , mitochondrial (6) and connective tissue (53) proteins. Our research group has applied intrinsically labelled protein to demonstrate that the ingestion of 20 g micellar casein protein results in the incorporation of approximately 2 g (about 10 %) dietary protein-derived amino acids into muscle tissue protein during a 5 h post-prandial period (3) .…”
Section: De Novo Muscle Protein Synthesismentioning
confidence: 99%